Pengaruh Madden Julian Oscillation (MJO) terhadap Sifat Hujan Tahunan 1990 – 2020 di 2X11 Kayu Tanam Sumatera Barat - Pancariniwati, Sri; Fadila, Riska; Melinda, Shelin (Stasiun Pemantau Atmosfer Global Lore Lindu Bariri - Palu, 2024)
Among the various atmospheric dynamics phenomena, there is an inter – seasonal phenomenon that has a major influence on rainfall variability in Indonesia, namely the Madden Julian Oscillation (MJO). In general, increased rainfall in Indonesia, especially West Sumatra, occurs when the MJO phase is active. This study will discuss the influence of the MJO on rainfall conditions in the 2x11 Kayu Tanam area which is reviewed from its nature in 4 Phases and 8 Phases. The results of the study show that the MJO amplitude above 1 indicates the influence of the MJO phase on increasing or decreasing rainfall compared to normal in 2x11 Kayu Tanam. Based on the division of the MJO into 4 phases (phases 2 – 3, 4 – 5, 6 – 7, and 8 – 1), the dominant MJO event that influences the increase in rainfall in 2x11 Kayu Tanam occurs in phase 2 – 3, while the dominant MJO event that influences the decrease in rainfall in 2x11 Kayu Tanam occurs in phase 6 – 7. Meanwhile, based on the division of MJO into 8 phases (1, 2, 3, 4, 5, 6, 7, and 8), the dominant MJO event that influenced the increase in rainfall in 2x11 Kayu Tanam occurred in phase 2, while the dominant MJO event that influenced the decrease in rainfall in 2x11 Kayu Tanam occurred in phase 6.